Lightening in a bottle: comparison of ultraviolet light to traditional sterilization in saline irrigations bottles. Issue 1 (10th October 2019) - Husain, Qasim; Banks, Catherine; Woodworth, Bradford A.; Bleier, Benjamin S.
Abstract : Background: Nasal saline irrigations (NSIs) are commonplace in treatment of patients with sinonasal disorders. Contamination of both the water source and delivery bottle remains a challenge with this therapy. The goal of this study was to optimize a disinfection technique with various methods of preparation, disinfection, and delivery of NSIs. Methods: Distilled and tap water sources in NSI bottles were contaminated by 4 bacterial strains: Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Legionella pneumophila . Contaminated bottles were cleaned with tap water, tap water with detergent, or microwave and swabbed for culture. Water‐source disinfection was performed with reverse osmosis, distillation, activated carbon filtration, boiling, or ultraviolet (UV) light treatment. Test samples from each experimental group (n = 3/group) were cultivated on the appropriate media with colony‐forming units (CFUs) reported. Results: All methods of bottle cleaning with tap water with/without detergent and microwave significantly reduced bacterial load (CFUs) by >99% ( p < 0.05). Distillation and boiling of the contaminated water source eliminated 100% of bacteria, whereas reverse osmosis and activated carbon filtration did not. A single UV treatment of contaminated water within a bottle eliminated 99% of bacteria within the water and 100% in the bottle. Conclusion: Cleansing of NSI bottles with tap water with/without detergent or microwave produced robust bacterial disinfection. Distillation and boiling of a contaminated water source completely eliminated all bacteria. UV light treatment was capable of simultaneous disinfection of both the water source and bottle, suggesting this may be a convenient, 1‐step method of preparing NSIs for patients.